The ability of Pichia kudriavzevii to tolerate multiple stresses makes it promising for developing improved bioethanol production processes. (1st July 2022) - Pongcharoen, Pongsanat
Abstract: Thermotolerant ethanol fermenting yeasts have been extensively used in industrial bioethanol production. However, little is known about yeast physiology under stress during bioethanol processing. This study investigated the physiological characteristics of the thermotolerant yeast Pichia kudriavzevii, strains NUNS‐4, NUNS‐5 and NUNS‐6, under the multiple stresses of heat, ethanol and sodium chloride. Results showed that NUNS‐4, NUNS‐5 and NUNS‐6 displayed higher growth rates under each stress condition than the reference strain, Saccharomyces cerevisiae TISTR5606. Maximum specific growth rates under stresses of heat (45°C), 15% v/v ethanol and 1·0 M sodium chloride were 0·23 ± 0·04 (NUNS‐4), 0·11 ± 0·01 (NUNS‐5) and 0·15 ± 0·01 h –1 (NUNS‐5), respectively. Morphological features of all yeast studied changed distinctly with the production of granules and vacuoles when exposed to ethanol, and cells were elongated under increased sodium chloride concentration. This study suggests that the three P. kudriavzevii strains are potential candidates to use in industrial–scale fermentation due to a high specific growth rate under multiple stress conditions. Multiple stress‐tolerant P. kudriavzevii NUNS strains have received much attention not only for improving large‐scale fuel ethanol production, but also for utilizing these strains in other biotechnological industries. Abstract: Significance and Impact of the Study: Multiple stresses are critical factors, hampering cell survival and ethanol production of thermotolerant yeast in bioethanol industry. It is important to characterize growth physiology of thermotolerant yeasts in extreme environments. In this study, the growth physiology and morphological features of the thermotolerant yeast Pichia kudriavzevii (strains NUNS‐4, NUNS‐5 and NUNS‐6) under stress conditions were investigated. Results showed that all strains investigated exhibited high growth under the stresses of heat, ethanol and osmotic pressure, although their morphological characteristic changed. Therefore, they are promising as yeast strains with the potential to be applied in industrial processes for bioethanol production.